2016
DOI: 10.1371/journal.pone.0156381
|View full text |Cite
|
Sign up to set email alerts
|

Serum Anion Gap Predicts All-Cause Mortality in Patients with Advanced Chronic Kidney Disease: A Retrospective Analysis of a Randomized Controlled Study

Abstract: Background and ObjectivesCardiovascular outcomes and mortality rates are poor in advanced chronic kidney disease (CKD) patients. Novel risk factors related to clinical outcomes should be identified.MethodsA retrospective analysis of data from a randomized controlled study was performed in 440 CKD patients aged > 18 years, with estimated glomerular filtration rate 15–60 mL/min/1.73m2. Clinical data were available, and the albumin-adjusted serum anion gap (A-SAG) could be calculated. The outcome analyzed was all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
(49 reference statements)
2
5
0
Order By: Relevance
“…In this study, we also showed that the traditional AG value was positively associated with both the leukocyte count and CRP level in patients with ESKD. The association between high AG, high CRP and a high leukocyte count and a low eGFR detected in this study may also support the increased risk of mortality by high AG, as previously reported 7 , 8 .…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we also showed that the traditional AG value was positively associated with both the leukocyte count and CRP level in patients with ESKD. The association between high AG, high CRP and a high leukocyte count and a low eGFR detected in this study may also support the increased risk of mortality by high AG, as previously reported 7 , 8 .…”
Section: Discussionsupporting
confidence: 91%
“…A retrospective analysis of 440 participants data suggested that adjusted serum anion gap is an independent risk factor for all -cause mortality in advanced CKD patients, with HR (95% CI) 2.968 (1.143–7.708). 19 The relationship between serum AG and mortality has been reported not only in adults but also in children. Kim and his team 20 reported that corrected AG in children at ICU admission was associated with mortality, with odds ratio (95% CI) 1.110 (1.06–1.17).…”
Section: Discussionmentioning
confidence: 99%
“…β2MG, which is a well-known representative marker of smaller mid-size UTs in patients undergoing maintenance dialysis, has recently been rediscovered as a novel filtration marker predicting CKD progression and mortality [ 8 ]. Additionally, an increased AG caused by retention of anionic UTs reflects the potential for progression of uremic syndrome in ESRD patients and has also been proven to be related to mortality around the commencement of dialysis [ 9 , 10 ]. Although each biomarker reflecting the accumulation of UTs has been proven to be related to poor prognosis in ESRD patients, it remains unknown whether the combination of these three biomarkers, reflecting accumulation of multiple specific UTs, shows a greater association with worsening prognosis.…”
Section: Introductionmentioning
confidence: 99%